(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
In the field of professional motivation, a positive attitude of the student to the chosen profession plays a crucial role, since this is due to the final goals of education. A positive attitude to the profession determines the formation of other private motivations in harmony with sufficient knowledge of this profession